Heme crystallization in a Chagas disease vector acts as a redox-protective mechanism to allow insect reproduction and parasite infection. - Caroline M Ferreira; Renata Stiebler; Francis M Saraiva; Guilherme C Lechuga; Ana Beatriz Walter-Nuno; Saulo C Bourguignon; Marcelo S Gonzalez; Patrícia Azambuja; Ana Caroline P Gandara; Rubem F S Menna-Barreto; Gabriela O Paiva-Silva; Marcia C Paes; et al. (Public Library of Science (PLoS), 2018)
Heme crystallization as hemozoin represents the dominant mechanism of heme disposal in blood feeding triatomine insect vectors of the Chagas disease. The absence of drugs or vaccine for the Chagas disease causative agent, the parasite Trypanosoma cruzi, makes the control of vector population the best available strategy to limit disease spread. Although heme and redox homeostasis regulation is critical for both triatomine insects and T. cruzi, the physiological relevance of hemozoin for these organisms remains unknown. Here, we demonstrate that selective blockage of heme crystallization in vivo by the antimalarial drug quinidine, caused systemic heme overload and redox imbalance in distinct insect tissues, assessed by spectrophotometry and fluorescence microscopy. Quinidine treatment activated compensatory defensive heme-scavenging mechanisms to cope with excessive heme, as revealed by biochemical hemolymph analyses, and fat body gene expression. Importantly, egg production, oviposition, and total T. cruzi parasite counts in R. prolixus were significantly reduced by quinidine treatment. These effects were reverted by oral supplementation with the major insect antioxidant urate. Altogether, these data underscore the importance of heme crystallization as the main redox regulator for triatomine vectors, indicating the dual role of hemozoin as a protective mechanism to allow insect fertility, and T. cruzi life-cycle. Thus, targeting heme crystallization in insect vectors represents an innovative way for Chagas disease control, by reducing simultaneously triatomine reproduction and T. cruzi transmission.